Cerebellar Atrophy and Changes in Cytokines Associated with the CACNA1A R583Q Mutation in a Russian Familial Hemiplegic Migraine Type 1 Family - Khaiboullina, Svetlana F.; Mendelevich, Elena G.; Shigapova, Leyla H.; Shagimardanova, Elena; Gazizova, Guzel; Nikitin, Alexey; Martynova, Ekaterina; Davidyuk, Yuriy N.; Bogdanov, Enver I.; Gusev, Oleg; van den Maagdenberg, Arn M. J. M.; Giniatullin, Rashid A.; et al. (Frontiers in Cellular Neuroscience, 2017)
Background. Immune mechanisms recently emerged as important contributors to migraine pathology with cytokines affecting neuronal excitation. Therefore, elucidating the profile of cytokines activated in various forms of migraine, including those with a known genetic cause, can help in diagnostic and therapeutic approaches. Methods. Here we (i) performed exome sequencing to identify the causal gene mutation and (ii) measured, using Bio-Plex technology, 22 cytokines in serum of patients with familial migraine (two with hemiplegic migraine and two with migraine with aura) from a Russian family that ethnically belongs to the Tatar population. MRI scanning was used to assess cerebellar atrophy associated with migraine in mutation carriers. Results. Whole-exome sequencing revealed the R583Q missense mutation in the CACNA1A gene in the two patients with hemiplegic migraine and cerebellar ataxia with atrophy, confirming a FHM1 disorder. Two further patients did not have the mutation and suffered from migraine with aura. Elevated serum levels of pro-inflammatory and pro-nociceptive IL-6 and IL-18 were found in all four patients (compared to a reference panel), whereas pro-apoptotic SCGF- and TRAIL were higher only in the patients with the FHM1 mutation. Also, cytokines CXCL1, HGF, LIF and MIF were found particularly high in the two mutation carriers, suggesting a possible role of vascular impairment and neuroinflammation in disease pathogenesis. Notably, some ‘algesic’ cytokines, such as β-NGF and TNFβ, remained unchanged or even down-regulated. Conclusion. We present a detailed genetic, neurological and biochemical characterization of a small Russian FHM1 family and revealed evidence for higher levels of specific cytokines in migraine patients that support migraine-associated neuroinflammation in the pathology of migraine.